Lysogenic reproductive strategies of viral communities vary with soil depth and are correlated with bacterial diversity. (May 2020) - Liang, Xiaolong; Zhang, Yingyue; Wommack, K. Eric; Wilhelm, Steven W.; DeBruyn, Jennifer M.; Sherfy, Andrew C.; Zhuang, Jie; Radosevich, Mark
Abstract: Increased awareness of the abundance and diversity of viruses in soils has led to a growing interest in soil virus ecology. This interest is in part fueled by a need to understand the mechanisms behind the transformation of carbon and nutrient elements within soil ecosystems and what role if any viruses play in these biologically mediated processes. To explore the virus-host distribution and diversity patterns in soil profiles, bacterial community composition and structure, viral and bacterial abundances, and the lysogenic fractions (LF) of bacterial communities were assessed. Enumeration of virus-like particles (VLPs) by epifluorescence microscopy, prophage-induction assays (mitomycin C-based), and bacterial 16S rRNA gene amplicon sequencing were used in this study. The abundances of both extractable VLPs and bacterial cells decreased with soil depth, but VLP abundances decreased more rapidly than bacterial abundances leading to an overall decreasing virus-to-bacteria ratio with depth. In contrast, LF increased with soil depth, indicating lysogeny became a more important reproduction strategy for autochthonous soil bacteriophages in subsurface soil. Significant shifts in bacterial community composition and diversity with soil depth were closely correlated with VLP abundance, virus-to-bacteria ratio, and LF. The results suggest that the viral abundance and replication strategies vary significantly in different soil depths and are linked to microbial host community composition in soil. Highlights: Viral and bacterial abundance and virus-to-bacteria ratio decreased with soil depth. The lysogenic fraction was greater in subsurface than surface soils. Bacterial community composition varied while diversity decreased with soil depth. Viral abundance, lysogenic fraction, and burst size were significantly correlated with bacterial community composition.